On the evaluation methods for scientific journals - Dávalos Sotelo, Raymundo (Instituto de Ecología, A.C., 2016)
Today there is a huge interest and wide discussions in the academic world to find effective methods of evaluation of the impact of the work of the scientists. It is argued here that the impact of the information generated by researchers has relevance beyond a mere accounting of citations to academic products. However, there remains the need to assess in a more immediate way the effect or influence of scientific work. The central argument of this contribution is that the number of citations generated by the engine Google Scholar (GS) represents a far more accurate and complete the work of individual researchers that FI impact Factor. Associated with GS, there is the concept of index h5. To see if there are any regularity in the proportion of citations between the two databases, a search for citations was made to articles for authors considered representative: Williams-Linera et al. and Yáñez-Arancibia et al. for being the most cited. The value of the coefficient of determination shows the extraordinary regularity of this relationship. In the case of the valuation of the journals, it is argued that the index h is the most appropriate to the JCR. We reiterate that the real impact of the research work is beyond the scope of academic work and is reflected in the use of information in remote areas of academia, but that have broad impact on society as for example, the information required to define the protected natural areas.